miRNA deregulation and relationship with metabolic parameters after Mediterranean dietary intervention in BRCA-mutated women - De Summa, Simona; Traversa, Debora; Daniele, Antonella; Palumbo, Orazio; Carella, Massimo; Stallone, Raffaella; Tufaro, Antonio; Oliverio, Andreina; Bruno, Eleonora; Digennaro, Maria; Danza, Katia; Pasanisi, Patrizia; et al. (Frontiers in Oncology, 2023)
Background: Breast cancer onset is determined by a genetics-environment interaction. BRCA1/2 gene alterations are often genetically shared in familial context, but also food intake and hormonal assessment seem to influence the lifetime risk of developing this neoplasia. We previously showed the relationship between a six-months Mediterranean dietary intervention and insulin, glucose and estradiol levels in BRCA1/2 carrier subjects. The aim of the present study was to evidence the eventual influence of this dietary intervention on the relationship between circulating miRNA expression and metabolic parameters in presence of BRCA1/2 loss of function variants. Methods: Plasma samples of BRCA-women have been collected at the baseline and at the end of the dietary intervention. Moreover, subjects have been randomized in two groups: dietary intervention and placebo. miRNA profiling and subsequent ddPCR validation have been performed in all the subjects at both time points. Results: ddPCR analysis confirmed that five (miR-185-5p, miR-498, miR-3910, miR-4423 and miR-4445) of seven miRNAs, deregulated in the training cohort, were significantly up-regulated in subjects after dietary intervention compared with the baseline measurement. Interestingly, when we focused on variation of miRNA levels in the two timepoints, it could be observed that miR-4423, miR-4445 and miR-3910 expressions are positively correlated with variation in vitaminD level; whilst miR-185-5p difference in expression is related to HDL cholesterol variation. Conclusions: We highlighted the synergistic effect of a healthy lifestyle and epigenetic regulation in BC through the modulation of specific miRNAs. Different miRNAs have been reported involved in the tumor onset acting as tumor suppressors by targeting tumor-associated genes that are often downregulated.